Hemorrhagic Stroke as the Manifestation of Neuropsychiatric Systemic Lupus Erythematosus - Kurniawan, Mohammad; Nurdin, Ilham; Rasyid, Al; Mesiano, Taufik; Hidayat, Rakhmad; Harris, Salim (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2023)
Stroke is a major cause of mortality and disability. It can be classified into ischemic stroke and hemorrhagic stroke. Systemic Lupus Erythematosus (SLE) is a systemic autoimmune disease that can cause neuropsychiatric systemic lupus erythematosus (NPSLE) complications, one of those manifests as stroke, which happens often in young adults. Ischemic stroke is more common in SLE patient, but hemorrhagic stroke can also ensue. We present a case of SLE in a young woman with left-sided hemiparesis and convulsion. After undergoing clinical evaluation, laboratory testing, and radiological imaging, she was diagnosed with hemorrhagic stroke. She was treated conservatively; blood pressure control, steroid administration to improve the condition, and anticonvulsants.